A minority within a minority : West Indian American response to race and ethnicity in New York City, 1900-1965 - Toney, Joyce (2000)
Examines some of the conditions that confronted people who had to identify at all times with both an ethnic group, and a racial minority. Focuses on two types of extreme response evident among West Indian immigrants viz. radical activism and the tendency of Caribbean migrants to isolate themselves in their ethnic clubs and organizations.